ANALYSIS OF TRIGLYCERIDE LEVELS AMONG E-CIGARETTE SMOKERS IN ADOLESCENTS FROM A HEALTH KNOWLEDGE PERSPECTIVE - Hanum, Galuh Ratmana; Mukarromah, Rizka Aisya; Yuliani, Resta Dwi (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aimed to analyze triglyceride levels among e-cigarette users at Universitas Muhammadiyah Sidoarjo. Method: A total of 32 male students who used e-cigarettes participated, and 3 cc of venous blood was drawn after at least 10 hours of fasting. Triglyceride levels were measured using a DIALAB Autolyzer with the enzymatic colorimetric method (GPO-PAP) and analyzed using the Independent t-test with SPSS 23.0. Results: The results showed an average triglyceride level of 86.75 mg/dl (range 63–125 mg/dl), which is within the normal category (<150 mg/dl). The hypothesis test showed p = 0.146 (p > 0.05), indicating no significant difference in triglyceride levels among e-cigarette users. Novelty: This study provides valuable insights into the triglyceride levels of e-cigarette users, contributing to the understanding of the potential impact of e-cigarette use on lipid profiles.